2010
DOI: 10.1002/mds.23407
|View full text |Cite
|
Sign up to set email alerts
|

Exercise elevates dopamine D2 receptor in a mouse model of Parkinson's disease: In vivo imaging with [18F]fallypride

Abstract: The purpose of the current study was to examine changes in dopamine D2 receptor (DA-D2R) expression within the basal ganglia of MPTP mice subjected to intensive treadmill exercise. Using Western immunoblotting analysis of synaptoneurosomes and in vivo positron emission tomography (PET) imaging employing the DA-D2R specific ligand [18F]fallypride, we found that high intensity treadmill exercise led to an increase in striatal DA-D2R expression that was most pronounced in MPTP compared to saline treated mice. Exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
91
3
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(104 citation statements)
references
References 37 publications
8
91
3
1
Order By: Relevance
“…In animal models, exercise produces the most pronounced effects on striatal dopaminergic markers in the dopaminedepleted compared with nondepleted striatum. In the MPTP animal model of Parkinson's disease, 6 weeks of treadmill exercise produces larger increases in D2/D3 BP ND in animals treated with MPTP than those treated with saline (Vuckovic et al, 2010). In rodent models of methamphetamine-induced dopamine depletion, exercise increases striatal levels of dopamine transporter and tyrosine hydroxylase in the methamphetamine-treated animals, with only minimal effects in saline-treated animals .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In animal models, exercise produces the most pronounced effects on striatal dopaminergic markers in the dopaminedepleted compared with nondepleted striatum. In the MPTP animal model of Parkinson's disease, 6 weeks of treadmill exercise produces larger increases in D2/D3 BP ND in animals treated with MPTP than those treated with saline (Vuckovic et al, 2010). In rodent models of methamphetamine-induced dopamine depletion, exercise increases striatal levels of dopamine transporter and tyrosine hydroxylase in the methamphetamine-treated animals, with only minimal effects in saline-treated animals .…”
Section: Discussionmentioning
confidence: 95%
“…Other studies have shown that wheel running attenuates methamphetamine-induced damage to serotonergic and dopaminergic terminals O'Dell et al, 2012), as well as D2/D3 dopamine receptor binding in a model of Parkinson's disease (Vuckovic et al, 2010). Moreover, in a pilot study of four patients with earlystage Parkinson's disease, striatal D2/D3 BP ND was increased in the two patients who engaged in treadmill exercise but not in the two patients who did not (Fisher et al, 2013).…”
Section: Introductionmentioning
confidence: 89%
“…Exercise is also able to modify dopamine and noradrenergic transmission as evidenced by increased tyrosine hydroxylase expression (Foley andFleshner, 2008, Kim et al, 2011), elevated striatal dopamine D2 receptor expression (Vuckovic et al, 2010) and increased noradrenaline levels (Dishman, 1997) in rats exposed to chronic exercise. However, acute exercise comprising 30 minutes of vigorous exercise in healthy adult volunteers with a history of regular exercise did not change synaptic dopamine concentrations (Wang et al, 2000).…”
Section: Exercise and Its Effect On Neurotransmittersmentioning
confidence: 99%
“…Many studies have supported the long-term benefits of exercise in humans, even in Alzheimer's and Parkinson's patients Xu et al 2010;Erickson et al 2012;Mayeux and Stern 2012;Fisher et al 2013;Intlekofer and Cotman 2013;Winchester et al 2013). Animal studies have also shown convincingly that exercise is protective in experimental models of neurodegeneration (for some examples, see Adlard et al 2005;Nichol et al 2009;Pothakos et al 2009;Zigmond et al 2009;Gerecke et al 2010;Vuckovic et al 2010;Intlekofer and Cotman 2013;Souza et al 2013). The studies on the benefits of long term exercise, dietary phytochemicals such as nicotine and caffeine, and moderate alcohol consumption all suggest that chronic adaptation to stress may be achievable in humans.…”
Section: Adaptation and Sensitization To Proteotoxic Stressmentioning
confidence: 99%